Tiludronate concentrations and cytologic findings in synovial fluid after intravenous regional limb perfusion with tiludronate in horses - Hunter, Barbara G.; Duesterdieck-Zellmer, Katja F.; Larson, Maureen K. (PeerJ, 2015)
Anecdotal accounts of tiludronate administration via intravenous regional limb perfusion (IVRLP) exist despite a lack of information regarding safety for synovial structures in the perfused area. The objective of this study was to determine whether tiludronate concentrations in synovial structures after IVRLP with low dose (0.5 mg, LDT) or high dose (50 mg, HDT) tiludronate remain below a value demonstrated in vitro to be safe for articular cartilage (<19,000 ng/ml), and to determine effects of tiludronate on synovial fluid cytology variables compared to saline perfused control limbs. Using a randomized controlled experimental study design, horses received IVRLP with LDT (n = 6) or HDT (n = 6) in one forelimb and IVRLP with saline in the contralateral limb. Synovial fluid cytology variables and tiludronate concentrations were evaluated in navicular bursae (NB), and distal interphalangeal (DIP) and metacarpophalangeal (MCP) joints one week before and 30–45 min after IVRLP, and in DIP and MCP joints 24 h after IVRLP. Data were analyzed with 2-way rmANOVA (p < 0.05). Highest measured synovial fluid tiludronate concentrations occurred 30–45 min post-perfusion. Mean tiludronate concentrations were lower in LDT limbs (MCP = 39.6 ± 14.3 ng/ml, DIP = 118.1 ± 66.6 ng/ml, NB = 82.1 ± 30.2 ng/ml) than in HDT limbs (MCP = 3,745.1 ± 1,536.6 ng/ml, DIP = 16,274.0 ± 5,460.2 ng/ml, NB = 6,049.3 ± 1,931.7 ng/ml). Tiludronate concentration was >19,000 ng/ml in DIP joints of two HDT limbs. Tiludronate was measurable only in synovial fluid from HDT limbs 24 h post-perfusion. There were no differences in synovial fluid cytology variables between control and treated limbs. Conclusions. In some horses, IVRLP with HDT may result in synovial fluid concentrations of tiludronate that may have adverse effects on articular cartilage, based on in vitro data. IVRLP with LDT is unlikely to promote articular cartilage degradation. Further studies to determine a safe and effective dose for IVRLP with tiludronate are needed.
Keywords: Intravenous regional limb perfusion; Synovial fluid; Horse; Tiludronate